The Role of Good Enough Parents and Gothic Parents in The Secret Garden - Kheradmand, Mahdieh (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Burnett's novel, The Secret Garden, offers a compelling exploration of the impact of parental influence on a child's development and the quest for Self. This article analyzes the role of gothic parents in shaping the lives of the protagonists, Mary and Colin, within the context of the novel's gothic elements. The narrative delves into the significance of family dynamics in shaping a child's Self. Drawing on psychological theories and literary analysis, the article highlights the pivotal role of good enough parents in providing a nurturing environment for children to develop their 'True Self'. Conversely, the absence or inadequacy of parental guidance leads to a gothic childhood fraught with loneliness, rejection, and a fragmented Self. By examining the interplay of gothic elements and parental influence in The Secret Garden, this study offers valuable insights into the complexities of childhood experiences and the enduring quest for Self.